THE EFFECT OF APPRECIATION IN THE WORKPLACE ON ACHIEVING ORGANIZATIONAL LOYALTY AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF EMPLOYEES OF THE UNIVERSITY OF KUFA - Lect. Hadeel Muhammad Ali; Lect. Ali sahib flayyih alabachee; Dr. Zaid Abdulzahra Jaffar (Scholar Express Journal, 2023)
The goal of the current study is to understand the nature of the relationship between organizational loyalty (OL) and appreciation in the workplace (AITW) among a sample of University of Kufa employees. The researchers used the random sample method and delivered 310 questionnaires to a mix of male and female employees in the aforementioned organization, one of the most significant in Iraq. The total number of questionnaires that were retrieved was (280), and of those, (273) were valid for statistical analysis. The response rate for the retrieved questionnaires was (97.5%), and they were examined using the statistical program (AMOS.25) and the advanced statistical program (SPSS.26). Theoretical findings indicated that there is a knowledge gap to explain the connection between corporate loyalty (OL) and appreciation in the workplace (AITW) in organizations generally.Keywords: appreciation in the workplace, organizational loyalty, University of Kufa
Keywords: workplace; number; University; Kufa